Renaissance and the Information Age of the Digital New Media: A Comparison: Exploring the Impact of Technology on the Renaissance Movement (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The period of sixteenth century England can perhaps be observed as one of the most tumultuous eras of all English history which witnessed and consolidated an impressive surge forward. Under the first Tudor monarch, Henry VII (reigned 1485-1509), England asserted itself as a power second to no other power in the world, seizing and establishing a cultural and political dominance over the world for which the reasons assigned are many.As we look back into the annals of time, in this case, the English Renaissance of the sixteenth century, it is important to contextualise and explicate the enterprise before embarking on the project. I comprehend two reasons for such a venture, that is, curiosity, appreciation, exhibition or examination of an era with its relevance to contemporary times. As my attempt will be to focus on the latter, I shall try to ascertain the impact of the growth of technology in ushering and propagating the Renaissance movement along with the growth of Humanism and try to see a parallel situation in the present epoch.